A time-window within the grain filling period accounted for early leaf senescence in maize under sink limitation - Dosio, Guillermo (2024)
In annual crops such as maize, assimilates demand exerted by grains converges with increasing leaf senescence. As sink demand changes as grains growth, leaf senescence could also be affected during the grain filling period. In this work, we evaluated the effect of a decrease in sinks demand at different moments of the grain filling period on maize leaf senescence. Sinks were modified in field experimentation via restriction of pollination or ear removal at four different times during the grain filling period. These growth and senescence-related-variables were periodically assessed: dry matter, stem carbohydrates, leaf initiation, leaf area, chlorophyll, sap flow and photosynthesis. Restriction of pollination and ear removal increased stem carbohydrates concentration and stem dry matter. Leaf senescence was accelerated only when ear was removed at R3 and R4 phenological stages. The magnitude of the effect was leaf position-dependent. A simple model relating leaf area duration or the area under the chlorophyll evolution curve with leaves age accounted for the observed results. Protecting grains during this window would avoid a decrease in grain yield both due to direct damage to the grains and the source reduction for advanced leaf senescence. These results would be of interest to producers, breeders and modelers of this crop.